2020
DOI: 10.1038/s41598-020-77604-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary n-3-PUFA supplementation, post-insemination plane of nutrition and pregnancy status on the endometrial transcriptome of beef heifers

Abstract: Supplementation of cattle diets with n-3-polyunsaturated fatty acids (PUFA) can improve reproductive efficiency. Conversely, short-term fluctuations in feed supply can impact pregnancy establishment. The objectives of this study were to examine the effects of (1) dietary supplementation with n-3-PUFA and (2) post-insemination plane of nutrition on the endometrial transcriptome. Beef crossbred heifers were offered concentrate based diets fortified with n-3-PUFA (PUFA; n = 32) or not (CONT; n = 28) for 30 days p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…In addition to dietary sources, for women of childbearing age, taking PUFA supplements may be beneficial for the treatment of menstrual dysfunction [ 13 ]. In animal experiments, researchers found that the addition of n-3 polyunsaturated fatty acids to the feed of heifers improved reproductive efficiency, and the study showed that n-3 polyunsaturated fatty acids had a positive effect on the expression of key genes during the window of implantation [ 14 ]. Lipid metabolism is required for uterine receptivity and embryo implantation [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to dietary sources, for women of childbearing age, taking PUFA supplements may be beneficial for the treatment of menstrual dysfunction [ 13 ]. In animal experiments, researchers found that the addition of n-3 polyunsaturated fatty acids to the feed of heifers improved reproductive efficiency, and the study showed that n-3 polyunsaturated fatty acids had a positive effect on the expression of key genes during the window of implantation [ 14 ]. Lipid metabolism is required for uterine receptivity and embryo implantation [ 15 ].…”
Section: Introductionmentioning
confidence: 99%